Evidence and Expertise in Nordic Education Policy A Comparative Network Analysis - Karseth, Berit; Sivesind, Kirsten; Steiner-Khamsi, Gita (Springer Nature, 2022)
This open access book explores how policy makers draw on national, regional and international expertise in issuing school reform within five Nordic countries. In an era of international comparison, policy makers are expected to review best practices, learn from experiences from elsewhere, and apply international standards propelled by international organizations. Do they do so? What counts, for them, as evidence and expertise? The chapters draw methodologically on bibliometric data, network analysis, document analysis and expert interviews. They show compellingly how governments use "evidence" strategically and selectively for agenda setting and policy decisions. This book will be of interest and value to scholars of education policy, specifically within the Nordic region, and international and comparative education.